Consolidations and Intercompany Bond Holdings. - Keister, Orville R. (The Accounting Review, 1967)
This article focuses on the difficulty in understanding the concept of consolidation eliminations by the students. Consolidation eliminations are necessary when a company's bonds are held by an affiliated company, even though the same students have little trouble with entries necessary to eliminate profits on intercompany inventory sales and fixed asset constructions. Because of this seemingly inevitable difficulty, for the past several years writers have expanded on the usual textual treatment in order to explain certain underlying relationships. This expansion results in much less confusion and a better basic understanding of why a given elimination entry is necessary. Students usually have no trouble understanding the 1/10th eliminations against bonds payable and discount on bonds payable and the need to eliminate the corresponding investment account. The consolidated entity must recognize an otherwise unrecognized loss on bond reacquisition. That is the nature of the charge or credit to retained earnings.